2022
DOI: 10.1039/d1nj04115k
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis via a one-pot approach and molecular docking studies of novel pyrrolo[2,1-a]isoquinoline derivatives

Abstract: This new investigation describes an efficient three-component approach for the stereoselective synthesis of pyrrolo[2,1-a]isoquinolines from readily available isatins, chalcones and 1,2,3,4-tetrahydroisoquinoline without using any metal catalyst or additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Literature reports clearly indicate isoquinoline moiety binds to Mtb enoyl reductase, [24] and hydrazide as key functional group has binding to Mtb peptide deformylase [25] . Hence, for molecular docking studies, we selected Mtb enoyl reductase and Mtb peptide deformylase as potential targets as the compounds designed in the current work are based on isoquinoline scaffold and has hydrazide as vital functional group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports clearly indicate isoquinoline moiety binds to Mtb enoyl reductase, [24] and hydrazide as key functional group has binding to Mtb peptide deformylase [25] . Hence, for molecular docking studies, we selected Mtb enoyl reductase and Mtb peptide deformylase as potential targets as the compounds designed in the current work are based on isoquinoline scaffold and has hydrazide as vital functional group.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, for molecular docking studies, we selected Mtb enoyl reductase and Mtb peptide deformylase as potential targets as the compounds designed in the current work are based on isoquinoline scaffold and has hydrazide as vital functional group. To authenticate the docking protocol implemented, the co‐crystal ligands of both the selected targets Mycobacterium tuberculosis enoyl reductase (InhA) PDB – 4TZK (co‐crystal ligand 641 ), [24] and Mycobacterium tuberculosis peptide deformylase PDB – 3E3U (co‐crystal ligand NVC20 ), [25] were extracted and redocked into the active site of the target protein. Further, the re‐docked ligands were overlaid with the respective X‐ray native pose of the co‐crystal ligand, and the RMSD was found to be below 2.0 Å ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, our group reported a method for the synthesis of Pyrrolo[2,1-a]isoquinoline derivatives 144 from readily available isatins 44, chalcones 143 and 1,2,3,4-tetrahydroisoquinoline in toluene under reflux condition(Scheme 26). [42] In this synthetic protocol initially, isatins 74 reacts with 1,2,3, The substrate scopes of this three-component coupling reaction were tested by using various substituted isatins 74 and chalcones 143 with 1,2,3,4-tetrahydro isoquinolineas a constant substrate scope and a series of pyrrolo[2,1a]isoquinoline derivatives 144 were synthesized in good yields (up to 87 %). Further, the synthetic methodology was also found to be equally successful with differently functionalized secondary amines such as pyrrolidine, piperidine and morpholine.…”
Section: Synthesis Of Pyrroles and Pyrrolidinesmentioning
confidence: 99%
“…Apart from this, a few modern reports also suggested that the putative mode of action of antimycobacterial tetrahydroisoquinoline derivatives is through inhibition of InhA of MTB. 29,36 Based on these reported facts and rationale, targeting the InhA enzyme followed by disruption of mycobacterial cellular homeostasis may be the appropriate strategy for the current molecular docking study and hence we have chosen Mycobacterium tuberculosis InhA (PDB ID: 4OHU), for the docking studies of the titled compounds.…”
Section: Molecular Docking Analysismentioning
confidence: 99%